An Analysis of Gender Inequality Bias in the Lyrics of Songs Composed by Denny Cak Nan - Dwi Nur Cahyani Sri Kusumaningtyas; Danang Wijoyanto; Yogi Bagus Adhimas; Arif Hidajad; Ajeng Dianing Kartika (International Journal of Language and Literature, 2025)
This study departs from the phenomenon of the widespread popularity of Javanese pop songs by Denny Cak Nan, which are widely consumed by the public yet contain problematic gender representations. The lyrics of selected songs, namely Los Dol, Satru, and Sugeng Dalu, frequently depict men as victims and women as sources of conflict, thereby reinforcing patriarchal perspectives within romantic relationships. The primary objective of this research is to reveal the embedded gender inequality and to demonstrate how popular media contributes to the normalization of gender stereotypes. This study employs a qualitative method with a feminist literary criticism approach. The research subjects consist of three selected songs by Denny Cak Nan, with data collected through documentation of the song lyrics. Validation was carried out through expert triangulation involving literary practitioners, academics, and researchers, while the instruments of analysis included the examination of diction, imagery, and narrative structure. The data were analyzed using critical discourse analysis to uncover the underlying gender ideology. The findings reveal a pattern of emotional manipulation, in which male characters are portrayed as deserving sympathy due to their suffering, while the roles and agency of women are marginalized. This research concludes that these lyrics function not merely as entertainment but also as a medium of ideological reproduction that shapes public perceptions of romantic relationships. The implications highlight the urgency of media literacy and gender awareness education to foster a more critical response to ideological messages conveyed through popular cultural products.